Ernest Becker and the psychology of worldviews - Webb, Eugene (Zygon, 1998)
Sheldon Solomon, Jeff Greenberg, and Tom Pyszczynski offer experimental confirmation for Ernest Becker's claim that the fear of death is a powerful unconscious motive producing polarized worldviews and scapegoating. Their suggestion that their findings also prove Sigmund Freud's theory of repression, with worldviews as its irrational products, is questionable, although Becker's own statements about worldviews as "illusions" seem to invite such interpretation. Their basic theory does not depend on this, however, and abandoning it would enable them to take better advantage of their finding that worldviews incorporating the values of rationality and tolerance tend to counteract polarization effects.